Innovative strategies towards effective teaching of career guidance and counselling in secondary schools - Monyake-Maja, Relebohile (Welkom: Central University of Technology, Free State, 2000)
This study was conducted in the Welkom District of the Free State. The sample of Grade 1 0 learners used during the empirical research, was taken mainly from the former Department of Education and Training schools which are still predominantly African. The problem investigated is whether career guidance and counselling can be improved in secondary school to the extend that leamers will benefit from it later in their lives and to address the needs of especially the African female leamers to equip them with skills to promote informed career choices. The study reveals that the educators themselves are not equipped to meet the demands of career guidance and counselling policy as formulated by the Department of Education. In the study the qualitative research approach is complemmted by participative action research (PAR). A pre- and post test was administered to establish whether learners benefited from the designed programme that was implemented during the PAR. Findings of the research were that there exists a total lack of sef and occupational knowledge as far as learners are concemed. The result is that learners choose subjects that do not ensure employment after school. Teachers are involved in the choices learners make ap.d in most cases parents decide for their children wlnt they should become in life and thus the Ieamer is not equipped by the school to make informed career choices. Both learners and parents still harbour career stereotypes where only nurturing kinds of employment is reserved for females and where the beief is that the wife should not earn more than the husband does. This study recommends that a programme that will address the above issues be implemented in the secondary schools, that stereotypes be eradicated, and that learners receive quality guidance teaching to enable them to make wise career choices. To this end teachers will have to receive intensive training.
Thesis
Keywords: Vocational guidance; Schools